(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It offers a decolonial analysis, situating the debate between environmental coloniality and the knowledge of the forest. It claims recognition of the Amazon as a political and epistemic subject, warning of the risks of a merely discursive visibility of the region. (Received: September 2025 | Accepted: October 2025)